The primary structure of human dopamine-beta-hydroxylase: insights into the relationship between the soluble and the membrane-bound forms of the enzyme. - Lamouroux, A (1987)
A full length dopamine-beta-hydroxylase (DBH) cDNA clone was isolated from a human pheochromocytoma lambda gt11 library. Both structural and functional evidence confirms the authenticity of the clone: (i) antibodies selected with fusion proteins generated by positive clones precipitate DBH activity, (ii) the sequence of three internal DBH tryptic peptides are included in the deduced DBH sequence, (iii) the previously reported N-terminal 15 amino acids of bovine DBH exhibits a nearly complete identity with that predicted for human DBH. The polypeptide chain of DBH comprises 578 amino acids corresponding to an unmodified protein of 64 862 daltons and is preceded by a cleaved signal peptide of 25 residues. DBH exists in both membrane-bound and soluble forms. The hydropathy plot reveals no obvious hydrophobic segment, except the signal peptide. S1 mapping analysis indicates no diversity in the 5' and 3' extremities of the DBH mRNA. Taken together with available biochemical data, these observations suggest that the membrane attachment of DBH probably results from a post-translational modification, glypiation being the most likely candidate. Comparative amino acid sequence analysis establishes that DBH shares no homology with the other catecholamine synthesizing enzymes, tyrosine hydroxylase and phenylethanolamine-N-methyl transferase.